Tourette’s Syndrome cervical dystonia induced occipital neuralgia remedied by peripheral nerve stimulation: A case report - Joseph, Crystal; Parkash, Anishinder; Gallagher, John; Chitneni, Ahish; Hirsh Kaveeshvar (Headache Medicine, 2023)
Background Dystonia is uncommon in Tourette’s syndrome, and occipital neuralgia secondary to Tourette's dystonia is more rare, affecting quality of life. Occipital peripheral nerve stimulation (PNS) is an excellent alternative by being adjustable and minimally invasive. Our case demonstrates occipital PNS as an effective option for refractory Tourette’s dystonia. Case Presentation A thirty-four-year-old male with poorly controlled Tourette’s cervical dystonia presented with severe occipital neuralgia. Various medications were prescribed including propranolol and amitriptyline, and bilateral third-occipital nerve rhizotomies and occipital nerve blocks were trialed. Distal nerve blocks at the occipital protuberance were most effective. Therefore, an occipital PNS trial was done, and a PNS was implanted with no complications. Upon follow-up, the patient reported drastic pain reduction. Conclusion Our case illustrates neuromodulation benefits for a rare presentation of refractory occipital neuralgia secondary to Tourette’s-related dystonia. Occipital PNS should be considered for refractory cases because it is safe, easy to implant, and effective.